THE POST-SOVIET STATE AND INSTITUTIONALIZATION OF ISLAM IN KABARDIN-BALKARIA - A. A. TATAROV (Кавказология, 2021)
Since the 1990s, the North Caucasus has experienced various conflicts between state and religious actors, sometimes with dreadful consequences. A comprehensive perspective on these outbursts of conflict is often constrained by the sole focus on the revival and internal dynamics of Islam in the post-Soviet period. The changes in the Russian state since the 2000s, which were in the nature of recentralization and strengthening of the state’s monopoly over violence and the state’s control over organizations, can be considered as an important factor influencing the legal existence of opposition groups or organizations. The case study of Kabardino-Balkaria, traditionally a stable republic of the North Caucasus, contributes to understandings of how the transformation of the state in Russia since the late 1990s influenced the development of religious conflict and the institutionalization of Islam.